Migration traps in disks around supermassive black holes - Bellovary, Jillian M.; Mac Low, Mordecai-Mark; McKernan, Barry; Ford, K. E. Saavik (The astrophysical journal. Part 2, Letters, 2016)
Accretion disks around supermassive black holes (SMBHs) in active galactic nuclei (AGNs) contain stars, stellar mass black holes, and other stellar remnants, which perturb the disk gas gravitationally. The resulting density perturbations exert torques on the embedded masses causing them to migrate through the disk in a manner analogous to planets in protoplanetary disks. We determine the strength and direction of these torques using an empirical analytic description dependent on local disk gradients, applied to two different analytic, steady-state disk models of SMBH accretion disks. We find that there are radii in such disks where the gas torque changes sign, trapping migrating objects. Our analysis shows that major migration traps generally occur where the disk surface density gradient changes sign from positive to negative, around 20-300Rg, where Rg = 2GM/c2 is the Schwarzschild radius. At these traps, massive objects in the AGN disk can accumulate, collide, scatter, and accrete. Intermediate mass black hole formation is likely in these disk locations, which may lead to preferential gap and cavity creation at these radii. Our model thus has significant implications for SMBH growth as well as gravitational wave source populations.